2020
DOI: 10.1021/acsami.0c13020
|View full text |Cite
|
Sign up to set email alerts
|

Water-Mediated Ionic Migration in Memristive Nanowires with a Tunable Resistive Switching Mechanism

Abstract: Memristive devices based on electrochemical resistive switching effects have been proposed as promising candidates for in-memory computing and for the realization of artificial neural networks. Despite great efforts toward understanding the nanoionic processes underlying resistive switching phenomena, comprehension of the effect of competing redox processes on device functionalities from the materials perspective still represents a challenge. In this work, we experimentally and theoretically investigate the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…[ 146 ] Furthermore, for this kind of configuration, the electronic/ionic transport contributions in resistive switching can be easily regulated thanks to adsorbing chemical species (such as moisture) on the NW surface. [ 148 ] Thanks to the Schottky barriers of different height between the NW and the electrodes, such devices can exhibit a self‐limited current that prevents Joule heating and that can be easily modeled with two back‐to‐back diodes and a variable series resistance. [ 149 ] Finally, short‐term plasticity effects can be modeled starting from a potentiation‐depression rate balance equation, where coefficients are exponentially dependent upon applied voltage, as is typical of ionic transport.…”
Section: Quantum Conductance Regime In Resistive Switching and Memris...mentioning
confidence: 99%
“…[ 146 ] Furthermore, for this kind of configuration, the electronic/ionic transport contributions in resistive switching can be easily regulated thanks to adsorbing chemical species (such as moisture) on the NW surface. [ 148 ] Thanks to the Schottky barriers of different height between the NW and the electrodes, such devices can exhibit a self‐limited current that prevents Joule heating and that can be easily modeled with two back‐to‐back diodes and a variable series resistance. [ 149 ] Finally, short‐term plasticity effects can be modeled starting from a potentiation‐depression rate balance equation, where coefficients are exponentially dependent upon applied voltage, as is typical of ionic transport.…”
Section: Quantum Conductance Regime In Resistive Switching and Memris...mentioning
confidence: 99%
“…The device returns to the HRS after such a reset process. Therefore, the device can achieve a reversible transition between HRS and LRS due to the formation and disconnection of conductive filaments with the fast Set and Reset processes, which is useful for logic operation and information storage. , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the device can achieve a reversible transition between HRS and LRS due to the formation and disconnection of conductive filaments with the fast Set and Reset processes, which is useful for logic operation and information storage. 54,55 The mechanism of the Ag/AZB:PMMA/FTO organic memristive device in this study can be described as follows. When a relatively low positive voltage (<1 V) is applied to the top electrode of the device (in the low voltage region), Ag + ions and electrons will move to the bottom and top electrodes, forming charged regions near their counter electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous works revealed that moisture also has a strong impact on the Ag + ionic migration mechanism on ZnO crystalline surfaces. [ 49 ] Indeed, theoretical and experimental investigation revealed that water species adsorbed on a crystalline ZnO surface (here represented by grain surfaces) are responsible for a decrease of the diffusion barrier of Ag + ions, facilitating the formation of the metallic filament underlying resistive switching events. The lowering of the diffusion barrier was shown to be related to a qualitative change of the diffusion mechanism of silver ions that, in presence of moisture, move from one water molecule to the next one by forming AgOH complexes that prevent their interaction with Zn atoms on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The lowering of the diffusion barrier was shown to be related to a qualitative change of the diffusion mechanism of silver ions that, in presence of moisture, move from one water molecule to the next one by forming AgOH complexes that prevent their interaction with Zn atoms on the surface. [ 49 ]…”
Section: Discussionmentioning
confidence: 99%